2016
DOI: 10.3748/wjg.v22.i39.8750
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative therapy in locally advanced esophageal cancer

Abstract: Esophageal cancer is an aggressive malignancy associated with dismal treatment outcomes. Presence of two distinct histopathological types distinguishes it from other gastrointestinal tract malignancies. Surgery is the cornerstone of treatment in locally advanced esophageal cancer (T2 or greater or node positive); however, a high rate of disease recurrence (systemic and loco-regional) and poor survival justifies a continued search for optimal therapy. Various combinations of multimodality treatment (preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
0
16
1
2
Order By: Relevance
“…Radiotherapy has been established as an effective local treatment for carcinomas . Preoperative radiotherapy is a promising treatment option to downstage initially unresectable tumors, increase the resection rate and improve the overall survival of patients, especially for patients with low rectal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy has been established as an effective local treatment for carcinomas . Preoperative radiotherapy is a promising treatment option to downstage initially unresectable tumors, increase the resection rate and improve the overall survival of patients, especially for patients with low rectal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of micrometastasis that leads to failure in curatively treated patients guided the investigation to explore the role of induction preoperative chemotherapy. The aim of preoperative chemotherapy is exterminating micrometastasis, downstage the tumor enhancing resectability, improve locoregional control and finally improve overall survival (8). But on the other hand, it exists the risk of progression disease and compromising definitive treatment.…”
Section: 2locally Advanced Ecmentioning
confidence: 99%
“…Exclusive RT in the neoadjuvant setting has been used in oesophageal cancer in the attempt to ameliorate the rate of negative circumferential margin during radical resections, to lower the rate of loco-regional failure and to improve survival [8]. Five randomized phase III trials investigated whether pre-operative RT followed by surgery might be more effective compared to surgery alone [8].…”
Section: Pre-operative Radiotherapymentioning
confidence: 99%
“…Pre-operative CT was shown to provide tumour downsizing and downstaging, to improve resectability rates, to eradicate micrometastatic disease, to improve loco-regional control and survival in oesophageal and GEJ tumours [8]. The meta-analysis by Sjoquist et al [12] reported that the all-cause mortality was significantly lower in patients submitted to pre-operative CT before surgery over surgery alone (HR 0.87; 95% CI 0.79-0.96; p = 0.005), with an estimated 5.1% survival difference at 2 years.…”
Section: Pre-operative Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation